FRI0277 ISCHEMIC AND SYSTEMIC SYMPTOMS IN GIANT CELL ARTERITIS PATIENTS, RESPONSE TO TOCILIZUMAB. (June 2019) - Calderón-Goercke, Monica; Loricera, J.; Prieto-Peña, D.; Aldasoro, Vicente; Castañeda, Santos; Villa-Blanco, Ignacio; Humbría, Alicia; Moriano, Clara; Romero-Yuste, Susana; Narváez, J.; Gomez-Arango, Catalina; Perez-Pampín, Eva; et al.
Abstract : Background: In Giant Cell Arteritis (GCA) two dominant cytokine clusters have been linked to disease activity, IL-6 – IL-17 axis (Th17) and IL-12 – IFN γ axis (Th1). The first one related to systemic symptoms and the second route responsible for ischemic symptoms. Tocilizumab (TCZ) performs its effect mainly by inhibiting Th17 axis and terminally Th1 route. Objectives: Our aim was to evaluate the effect of TCZ on ischemic and systemic symptoms throughout the follow-up. Methods: Retrospective, multicenter study of 134 patients diagnosed of GCA on treatment with TCZ. We evaluate the efficacy of TCZ by improving ischemic (visual involvement, headache, jaw claudication) and systemic symptoms (fever, constitutional syndrome, polymyalgia rheumatica (PMR)). Results: We evaluated 134 patients (101 w/33 m) and its main symptoms at TCZ onset, TABLE. 73 (54.5%) patients presented PMR followed by headache in 70 (52.2%) cases, constitutional syndrome in 31 (23.1%) and visual involvement in 28 (20.9%) patients. After one month of treatment there was an important clinical improvement, persisting in 13, 6% of patients PMR, 10.6% headache and 10.6% visual involvement. Throughout the follow-up, the improvement of ischemic symptoms was slower. At month 12, in 5.6% (4) of patients persisted with visual impairment, and 2.8% (2) patients presented headache and constitutional syndrome. However, the analytical improvement was statistically significant from the first month and sustained during follow-up. Conclusion: According to the results of our study, we can conclude that in clinical practice, ischemic symptoms take longer to improve than systemic symptoms; being visual affectation the most frequent symptom after 12 months of follow-up. References: [1] Soriano A, Muratore F, Pipitone N, Boiardi L, Cimino L, Salvarani C. Visual loss and other cranial ischaemic complications in giant cell arteritis. Nat Rev Rheumatol. 2017; 13:476-84. [2] Ciccia F, Rizzo A, Ferrante A, Guggino G, Croci S, Cavazza A, et al. New insights into the pathogenesis of giant cell arteritis. Autoimmun Rev. 2017; 16:675-83. [3] Calderón-Goercke M. Tocilizumab in giant cell arteritis. Observational, open-label multicenter study of 134 patients in clinical practice. Semin Arthritis Rheum. 2019Jan5. pii: S0049-0172(18)30571-7. Doi: 10.1016/j.semarthrit.2019.01.003. [Epub ahead of print] Disclosure of Interests: Monica Calderón-Goercke: None declared, J. Loricera: None declared, D. Prieto-Peña: None declared, Vicente Aldasoro: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Ignacio Villa-Blanco: None declared, Alicia Humbría: None declared, Clara Moriano: None declared, Susana Romero-Yuste: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Catalina Gomez-Arango: None declared, Eva Perez-Pampín: None declared, Rafael Melero: None declared, Elena Becerra-Fernández: None declared, Marcelino Revenga: None declared, Noelia Alvarez-Rivas: None declared, Carles Galisteo: None declared, Francisca Sivera: None declared, Alejandro Olive: None declared, María Álvarez del Buergo: None declared, Luisa Marena Rojas: None declared, Carlos Fernández-López: None declared, Francisco Navarro: None declared, Enrique Raya: None declared, Eva Galindez: None declared, Beatriz Arca: None declared, Roser Solans-Laqué: None declared, Arantxa Conesa: None declared, Cristina Hidalgo: None declared, Carlos Vázquez: None declared, Jose Andrés Román-Ivorra: None declared, Pau Lluch: None declared, Sara Manrique Arija Speakers bureau: ABBvie, MSD, Janssen, Lillly, Roche, Pfyzer, Novartis., Paloma Vela-Casasempere Grant/research support from: UCB, Abbvie, Pfizer, Roche, Bristol-Myer-Squibb (another research, not BIOBADASER related), Consultant for: UCB, Lilly, Pfizer, Roche, Bristol-Myer-Squibb, Speakers bureau: Roche, UCB, MSD, Pfizer, GSK, BMS, Lilly, Eugenio de Miguel: None declared, Carmen Torres-Martín: None declared, Juan Carlos Nieto: None declared, Carmen Ordas-Calvo: None declared, Eva Salgado-Pérez: None declared, Cristina Luna-Gomez: None declared, Francisco J. Toyos Sáenz de Miera: None declared, Nagore Fernández-Llanio: None declared, Antonio García: None declared, Carmen Larena: None declared, Natalia Palmou-Fontana: None declared, Vanesa Calvo-Río: None declared, Carmen González-Vela: None declared, Alfonso Corrales: None declared, María Varela-García: None declared, Elena Aurrecoechea: None declared, Raquel Dos-Santos: None declared, Ángel García-Manzanares: None declared, Norberto Ortego: None declared, Sabela Fernández: None declared, Francisco Ortiz-Sanjuán: None declared, Montserrat Corteguera: None declared, J. Luis Hernández: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Ricardo Blanco Grant/research support from: Abbvie, MSD, and Roche, Consultant for: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen